La fábula: Estrategia didáctica para la comprensión lectora en niños del tercero de básica del cantón Montalvo, Los Ríos - Chang Morales, Magdalena del Rocío (2024)
Currently, there is a loss of reading habits in students, which leads to serious problems whose solution, if not proceeded in time, becomes irreversible. An example is the consequent loss of reflective interpretation abilities of the contents and the deficit of critical thinking. The use of fables as a pedagogical tool to improve children's reading comprehension is one of the didactic strategies that has been the object of interest in the educative community. The objective of this research is to analyze the fable as a didactic strategy within the teaching and learning process, to strengthen reading comprehension in children in the third ear of the John F. Kenned School of Basic Education. Research was developed based on the quantitative, correlational approach. Where a survey was applied to diagnose reading comprehension in 16 children. Which showed that seventy-five percent had comprehension difficulties. To solve this, seven reading workshops were developed with the fable as a resource, subsequently an exam was applied, its results show that eight one percent of the students achieved a development of reading comprehension at a literal, inferential and analytical level. There was also an increase in communication skills, psychological, emotional, and spiritual development. What confirms the hypothesis.